Heat tolerance evaluation of transgenic cotton germplasms with insect resistance and herbicide tolerance - CHINDUDZI Elmon; SU Bangrong; GUO Yi; ZHONG Zhentao; MAKONI Jane; ZHU Shuijin; CHEN Jinhong (浙江大学学报. 农业与生命科学版, 2019)
Heat stress has increasingly become a global problem affecting agriculture including cotton production which is a critical fiber and oil crop. The purpose of this study was to evaluate six transgenic insect-resistant and herbicide-tolerant cotton germplasms (HNZ 1063, HNZ 1068, HNZ 1073, HNZ 1081, HNZ 1088 and HNZ 1091) and the conventional cultivar Zhongmiansuo 49 (ZMS 49) based on the evaluation and screening of membrane thermostability, pollen viability and chlorophyll stability of field plants as an initial study. A follow up study was conducted using four-week-old seedlings treated at 42℃ (light)/24℃ (dark) for one week to further evaluate heat tolerance by measuring and analyzing photosynthetic rate, chlorophyll content, antioxidant enzyme activity and growth parameters. The results showed that three germplasms, HNZ 1091, HNZ 1068 and ZMS 49, were more heat-tolerant, while two, HNZ 1081 and 1073, were less tolerant. It can thus be concluded that there are differences in heat tolerance among different transgenic lines inserting the same gene.